The Correlation Between the Leadership Style of the Head Nurse and Staff Nurses’ Performance in a Hospital - Mhaezar, Adnan; Nurindasari, Sri; Suandi, Suandi; Awalia, Nurhikma (Advances in Healthcare Research, 2024)
Purpose: To examine the correlation between the leadership style of head nurses and the performance of staff nurses at Labuang Baji Regional Hospital. Research Design and Methodology: This study used a quantitative cross-sectional design involving 48 nurses selected through purposive sampling at Labuang Baji Regional Hospital, Makassar. Data were collected using a leadership style questionnaire and an observation checklist for nurse performance in documenting care. The independent variable was leadership style, and the dependent variable was nurse performance. Data were analyzed using linear regression with a significance level of p ≤ 0.005. Findings and Discussion: The dominant leadership style was autocratic (77.08%), and nurse performance in documentation was moderate primarily (81.25%). A moderate positive correlation was found between leadership style and nurse performance (r = 0.399). This suggests that leadership style has an impact on nurse performance. Improving leadership through training may enhance documentation quality. Implications: Improving head nurses’ leadership skills may enhance nurse performance and documentation quality. Leadership training is recommended.